2019
DOI: 10.33225/jbse/19.18.254
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Students’ Conceptions About Owls, Experiences With Owls and Their Sources of Information

Abstract: The present research explores benefits of using young students’ drawings in combination with written responses for gathering information about science concepts. Younger students are still very limited in their verbal expression and less biologically literate than older students. The aim was to determine primary school students’ conceptions about owls, experiences with owls and their sources of information, and to then determine how beneficial it is to combine information gathered from drawings and written resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In addition, the data are presented in Tables 1 and 2 as shown in the findings section. Torkar et al (2019) and Gnidovec and Torkar (2019) were used while creating the tables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the data are presented in Tables 1 and 2 as shown in the findings section. Torkar et al (2019) and Gnidovec and Torkar (2019) were used while creating the tables.…”
Section: Discussionmentioning
confidence: 99%
“…Ten students were randomly selected for interviews from among students who completed the drawings and written responses. Interviews were conducted with open-ended questions about appearance of owls, students' attitudes toward owls and symbolic representations of owls (Torkar and Bajd, 2006;Torkar et al, 2019;Gnidovec and Torkar, 2019).…”
Section: Data Collection Tool and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results of interviews with students, it can be concluded that some students had not been able to explain the science concept descriptively . Elementary school students' difficulties in explaining science concepts were because they were still at a very young age who had minimal verbal abilities in gathering information (Gnidovec & Torkar, 2019). The difficulties can be overcome by having a learning environment and technology that fits the context for elementary school students.…”
Section: Discussionmentioning
confidence: 99%
“…Younger students have limited ability to express information processing about science concepts verbally. However, students who have a better learning experience will be able to describe information about the science concept as a whole (Gnidovec & Torkar, 2019). NGSS shows changes in instruction used in science education lead to inquiry skills (Hoisington, 2018).…”
Section: Introductionmentioning
confidence: 99%